Ultimate strength and fracture sequence of bolted connections to thin-walled carbon steel. (February 2020) - Mahmood, Mohammed; Elamin, Ahmed; Tizani, Walid
Abstract: Recent experimental studies on single shear bolted connections to thin-walled carbon steel indicated the need for parametric analysis to understand the behaviour of the connection. In this paper, finite element analysis was performed to investigate the ultimate behaviour and failure sequence of these connections. A parametric analysis was performed to investigate the effect of plate thickness, end distance and curling displacement on the connection behaviour. Five possible modes of failure were identified and analytical models for estimating the connection strength for these modes were proposed. Within the range of the validity of the study, the end distance was the most influential parameter, but the strength improvement becomes negligible at edge distance of 42 mm for plate thickness less than or equal to 3.5 mm and 48 mm for plate thickness greater than 3.5 mm. Therefore, it is recommended to limit the maximum end distance to 50 mm. The curling displacement is found to affect the stress distribution in the plate as it could reduce the connection strength by 12%. It is considered as a sign of failure only when it reaches 0.5 mm before the ultimate strength of the connection is reached. The proposed models are more accurate in predicting the connection ultimate strength when compared to EC3, AISI and AISC predictions.